Overcoming Photo Degredation in Dye Sensitized Solar Cell - Odeyemi Charity Segun; Awodugba Awodugba; Ayodeji Oladiran (IAES Indonesian Section, 2018)
Dye sensitized solar cell (DSSC) is a thin film solar cell which has prospect for solving the fast growing global energy demand. It uses basically titanium dioxide TiO2, organic dye and electrolyte. The availability of these materials and their low cost makes DSSC the cheapest solar cell in the world. Although efforts are being made to improve efficiency but the short life span remain a major challenge. Improving this short life span is what this study is responding to. A known method of preparation was examined and modified for better DSSC performance. Two new approaches were introduced to the process of DSSC fabrication: the introduction of a mordant and sealing the edges. The organic pigment used for light harvesting was Teak dye. The results of the conventional method and the modified method were obtained and compared. The results of the newly developed method show a very wide improvement in the DSSC life span, and even some improvement in the efficiency. The active period of the cell increase to 60 days while the one made with the conventional approach degraded after four hours. Through these modifications, a new procedure for producing DSSC has been developed which will solve the problem of short active period in dye sensitized solar cell.